2020
DOI: 10.3390/app10072439
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove Soil-Borne Trace Elements in Qi’ao Island: Implications for Understanding Terrestrial Input of Trace Elements into Part of the Pearl River Estuary

Abstract: An investigation was conducted to characterize the trace element status of mangrove soils of Qi’ao Island in the Pearl River estuary. The results show that the spatial variation in the soil-borne trace elements in the investigated area was minor and most of the trace elements were at a level higher than those in other mangrove wetlands around the world, suggesting the mangrove soils of Qi’ao Island were heavily contaminated by trace elements transported from the Pearl River in the past two decades. Zn was clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The current study showed that Cd, Zn, Cu and Pb were the dominant heavy metals at the investigated Futian mangrove soils according to their levels against the thresholds set for Class I marine sediment equality in the National Standard of China [15]. This is in good agreement with other published work showing that Cd, Cu and Zn were the major heavy metals in the Pearl River Estuary [19,20]. The more heavily contaminated status in Locations 1-4 than in Locations 5-8 was previously noted by Li et al [21] and Xu et al [16].…”
Section: Discussionsupporting
confidence: 92%
“…The current study showed that Cd, Zn, Cu and Pb were the dominant heavy metals at the investigated Futian mangrove soils according to their levels against the thresholds set for Class I marine sediment equality in the National Standard of China [15]. This is in good agreement with other published work showing that Cd, Cu and Zn were the major heavy metals in the Pearl River Estuary [19,20]. The more heavily contaminated status in Locations 1-4 than in Locations 5-8 was previously noted by Li et al [21] and Xu et al [16].…”
Section: Discussionsupporting
confidence: 92%
“…Considering all the toxic elements in the soil, the Integrated Nemerow Pollution Index (INPI) can be calculated based on Equation (12) for each sampling station (Niu et al, 2020). 3) and class 4, highly polluted (INPI ≥ 3).…”
Section: -Pollution Load Index (Pli)mentioning
confidence: 99%
“…The Contamination Degree (C D ) includes the total PI for each element (Nazzal et al, 2013) Considering all the toxic elements in the soil, the Integrated Nemerow Pollution Index (INPI) can be calculated based on Equation ( 12) for each sampling station (Niu et al, 2020).…”
Section: = ∑ =1mentioning
confidence: 99%